On two recent attempts to introduce animal spirits in macroeconomics: Heresy or enlightened church reform? - Togati, Teodoro Dario (PSL Quarterly Review, 2021)
As noted by Alan Greenspan in 2008, one key flaw in standard models is that they treat animal spirits as a simple ‘add factor’ rather than as a structural one. This paper evaluates the extent to which two recent approaches placing the emphasis on animal spirits – namely Farmer’s ‘Neo-Paleo-Keynesian’ (NPK) project and Akerlof and Shiller’s behavioural approach – manage to overcome this flaw. By following the powerful religious metaphor introduced by Farmer, according to which general equilibrium theory underlying standard models should be regarded as a ‘church’, this paper stresses two points. First, animal spirits turn out to be devilish features that are inconsistent with the church’s commandments. Second, by trying to reconcile them with the church, these two approaches are unable to truly reform it as required by Greenspan; rather, they appear to be heretical stances that are forced to violate some fundamental dogmas of the church. JEL codes: E12, E13, E32 Keywords: Animal spirits, general equilibrium, research programmes, Keynesian economics, macroeconomic models